Karmienie naturalne - cenny dar i kamień milowy opieki nad noworodkiem = Natural feeding - precious gift and mile stone in care of the newborn - Jasik, Justyna (Zielona Góra: Lubuskie Towarzystwo Naukowe)
Breastfeeding is an optimal way of feeding which provides full health and proper evelopment of each newborn baby, regardless of race, culture and socioeconomic conditions in a particular country. Carl von Linne, the author of taxonomy, wrote a masterpiece on species classification. He perceived breastfeeding so peculiar for the particular group of animal organisms (including people) that he called them mammals (Latin: mamma, i.e. breast).
Keywords: lactation; maternal milk; lactation difficulties; education; laktacja; mleko matki; edukacja